Uji Efektivitas Antimikroba Beberapa Merek Dagang Pembersih Tangan Antiseptik - Radji, Maksum; Suryadi, Herman; Ariyanti, Dessy (Majalah Ilmu Kefarmasian, 2007)
In Modern life, peoples are more conscious to keep their healthy. One of the way to keep our body healthy is by keeping our hand clean. Washing hands with soap and water, sometimes is unpractical since it need water to rinse off the soap. Prod-uct innovation has been developed to overcome the unpractical side, which is called antiseptic hand wash or hand sanitizer. This study has been done to evaluate the antimicrobial activity of some hand sanitizer products marketed in Jakarta. The re-sult showed that alcohol-based hand sanitizer and triclosan-based hand sanitizer used in this experiment were significantly reduce bacterial counts on hands, but not all of the samples are effective in reducing fungal counts on hands.